2016
DOI: 10.1177/0884533616662996
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fat Emulsion Formulations for the Adult and Pediatric Patient

Abstract: Intravenous lipid emulsions (IVLE) provide essential fatty acids (FA) and are a dense source of energy in parenteral nutrition (PN). Parenterally administered lipid was introduced in the 17th century but plagued with side effects. The formulation of lipid emulsions later on made it a relatively safe component for administration to patients. Many ingredients are common to all IVLE, yet the oil source(s) and its (their) percentage(s) makes them different from each other. The oil used dictates how IVLE are metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 132 publications
2
97
1
4
Order By: Relevance
“…A new IV fat emulsion product containing a combination of soybean oil, olive oil, fish oil, and medium‐chain triglycerides has been approved by the Food and Drug Administration (FDA) for use in the United States. Although its use is currently limited, clinical studies have shown this IV fat emulsion to have less inflammatory properties, high antioxidant content, and decreased risk of cholestasis in HPN‐dependent patients 61 …”
Section: Long‐term Metabolic Complicationsmentioning
confidence: 99%
“…A new IV fat emulsion product containing a combination of soybean oil, olive oil, fish oil, and medium‐chain triglycerides has been approved by the Food and Drug Administration (FDA) for use in the United States. Although its use is currently limited, clinical studies have shown this IV fat emulsion to have less inflammatory properties, high antioxidant content, and decreased risk of cholestasis in HPN‐dependent patients 61 …”
Section: Long‐term Metabolic Complicationsmentioning
confidence: 99%
“…Another limitation to generalizability was that many patients used an investigational lipid emulsion Omegaven (Fresenius Kabi AG, Bad Homburg vdh, Germany). Omegaven requires specific administration techniques as it is dispensed in 100 ml bottles and is not available as a total nutrient admixture, thus requiring the use of an additional infusion pump and a different administration set with a vented spike . A final limitation is that it is difficult to control for all non‐HPN factors that contribute to postdischarge adverse events such as readmission.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, work by Schubert and Wretlind 12 showed that the use of SO stabilized with egg yolk phosphatides in 2.5% glycerol solution caused no significant reactions, leading to the introduction and acceptance of Intralipid (produced by Fresenius Kabi [Bad Homburg, Germany] and sold by Baxter [Deerfield, IL] in the United States) in the United Kingdom, France, and Scandinavia in 1961. In the United States, Intralipid did not receive Food and Drug Administration (FDA) approval until 1972, leading to the continued use of high‐dextrose, lipid‐free PN 13 . Subsequent reports began to link this PN formulation to hyperosmolar hyperglycemic nonketotic diabetic coma, hepatic enzyme elevations, fatty liver, and EFAD, especially in children 14 – 19 .…”
Section: So Ifementioning
confidence: 99%